2021
DOI: 10.1038/s43587-021-00105-8
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin remodeling due to degradation of citrate carrier impairs osteogenesis of aged mesenchymal stem cells

Abstract: Aging is accompanied by a general decline in the function of many cellular pathways. However, whether these are causally or functionally interconnected remains elusive. Here, we study the effect of mitochondrial–nuclear communication on stem cell aging. We show that aged mesenchymal stem cells exhibit reduced chromatin accessibility and lower histone acetylation, particularly on promoters and enhancers of osteogenic genes. The reduced histone acetylation is due to impaired export of mitochondrial acetyl-CoA, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 70 publications
5
39
0
Order By: Relevance
“…Plotting nucleosome occupancy over the TSS of all protein-coding genes confirmed that atmospheric oxygen resulted in higher nucleosome density around the promoter region, but more importantly, confirmed the reduced chromatin accessibility at the TSS ( Figure 2e) . Feature distribution analysis, using promoter proximity criteria to call gene promoters and previously published enhancer regions in MSCs (Pouikli et al, 2021) to identify potential enhancers, confirmed that the vast majority of closing peaks in normoxia-cultured cells were found in gene regulatory elements i.e., promoters and enhancers ( Figure 2f) . This strong decrease in chromatin accessibility at the TSS was also visible on a single gene level.…”
Section: Resultssupporting
confidence: 64%
See 4 more Smart Citations
“…Plotting nucleosome occupancy over the TSS of all protein-coding genes confirmed that atmospheric oxygen resulted in higher nucleosome density around the promoter region, but more importantly, confirmed the reduced chromatin accessibility at the TSS ( Figure 2e) . Feature distribution analysis, using promoter proximity criteria to call gene promoters and previously published enhancer regions in MSCs (Pouikli et al, 2021) to identify potential enhancers, confirmed that the vast majority of closing peaks in normoxia-cultured cells were found in gene regulatory elements i.e., promoters and enhancers ( Figure 2f) . This strong decrease in chromatin accessibility at the TSS was also visible on a single gene level.…”
Section: Resultssupporting
confidence: 64%
“…Despite the oxygen-driven metabolic rewiring which results in production of high acetyl-CoA levels, histone hypo-acetylation occurs due to trapping of acetyl-CoA inside the mitochondria of normoxia-cultured cells, indicating that the functionality of citrate carrier (CiC) is impaired at high oxygen. Remarkably, similar changes were observed in ageing MSCs, suggesting that high oxygen mimics the physiological process of ageing with regards to the role of the mito-nuclear communication in the regulation of stem cell differentiation (Pouikli et al, 2021).…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations